(untitled) (Brazilian Journal of Radiation Sciences, 2019)
The so-called “Control Blade History” (CBH) effect has always posed a serious challenge for any nodal core simulator in performing Boiling Water Reactor (BWR) core analyses. In this paper a method to handle such CBH effects is proposed based on the idea of interpolating lattice physics data between two extreme cases with regard to CBH, namely, the case with the control rod always inserted during depletion and the case with the control rod never inserted during fuel irradiation. In POLCA8, the latest upgrade of the Westinghouse BWR nodal core simulator POLCA, one applies the methodology to macroscopic cross sections, discontinuity factors, pin powers and detector constants. Overall, the proposed CBH model performs very well in terms of predictive accuracy of reactivity and pin powers although simultaneous presence of control rods (CRs) and burnable absorbers (BAs) still poses a challenge due to some observed interference of their impact on reactivity. Applying the CBH model for pin power reconstruction is particularly promising and provides excellent prediction accuracy in the vicinity of the CR and at the point of CR withdrawal being the most challenging and critical condition with regard to CBH.